Extracellular vesicles as a source for non-invasive prostate cancer biomarkers - Mäkelä, Kristiina (My University, 2022)
Prostate cancer (PCa) is the third most frequent cancer diagnosis worldwide. Lack of specificity and sensitivity in the current “golden standard” diagnostic approach has motivated researchers to look for new biomarkers, that could better distinguish between indolent and life-threatening forms of PCa, especially in the early stages of the disease. Extracellular vesicles (EVs) are cell-secreted membranous particles, that carry information about their parent cells' pathophysiology. This makes the extracellular vesicles in urine (uEV) promising non-invasive indicators for urogenital tract disorders, including PCa. The goal of this study is to identify tumor-associated glycans or protein epitopes on the surface of uEVs from PCa patients using a nanoparticle-assisted time- resolved fluorescence immunoassay (NP-TRFIA) with various glycan-binding lectins or tumor-associated antibody markers. This NP-TRFIA tests a variety of antibodies and lectins to determine the right biomarker combination for distinguishing between urine samples of healthy, benign, and cancerous origin. Capture and tracer that both target integrin alpha unit 4 (ITGA4/CD49d) were shown to be the most effective in distinguishing between individual benign and PCa samples and this difference was statistically significant (p-value = 0.04). These preliminary findings support the use of uEVs as a source of non-invasive PCa biomarkers and imply that the NP-TRFIA method provided here has the ability to detect tumor-associated glycosylation patterns in uEVs with increased sensitivity from minimally processed urine samples. However, more research and assay optimization are still required. With the optimal combination of capture and tracer, this assay format could be used as a liquid biopsy-based test for screening, diagnosis, and monitoring of PCa in the future.
Keywords: prostate cancer, diagnostics, biomarker, glycosylation, extracellular vesicle, EV, NP-TRFIA, nanoparticle, immunoassay, liquid biopsy